Roboldo: An Affective Robot for Empathetic Social Interactions in Education - Souza, Anderson; Sousa, Carlos Eduardo; Torres, Daniel; Paradeda, Raul (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
Educational robotics has become a highly relevant tool in the current educational scenario, with a growing number of robotic agents being used to assist in teaching subjects such as mathematics, logic, and other areas of science. However, most of these agents do not have social or emotional characteristics, limiting their potential for application in different areas of knowl-edge, such as history, literacy, and biology, which could benefit from more interactive and emotionally engaging approaches. This article proposes a new approach to educational robotics by introducing a robot with emotional intelligence, designed to interact in a playful and empathetic way. The construction of the robot combines elements of low-cost electronics, artificial intelligence, and emotional design, with the aim of creating a teaching tool that goes beyond supporting exact subjects, promoting a richer and more diverse educational experience. This study covers aspects from the design of the robot to its implementation and initial evaluation, focusing on the expression and recognition of emotions, as well as the robot's ability to interact with individuals of different ages in different contexts.